Do Democracy and Press Freedom Reduce Corruption? Evidence from a Cross Country Study - Shyamal K. Chowdhury (ZEF - Discussion Papers on Development Policy 85, 2004)
This paper calls attention to the instrumental role of democracy and press freedom in combating corruption. As opposed to an autocracy with no or limited press freedom, a free press in a democracy can inform voters about the corruption of political representatives, and voters in turn can punish incumbents by electing opposition parties. The empirical investigation carried out in this paper shows that democracy and press freedom can have significant impact on corruption. Though corruption may persist in the short- to medium-run, an increase in voters' participation and press freedom can reduce corruption.